Robotic tools provide better assistance to crisis intervention teams.
Local authorities and emergency services often face the challenge of effectively managing catastrophes such as earthquakes and tsunamis. The EU has funded new tools and crisis management solutions for saving human lives and speeding up the search and rescue process.